The Effect of Good Corporate Governance and Intellectual Capital on Financial Performance - Faeni, Dewi Puspaningtyas (International Journal of Business Studies, 2024)
The purpose of this study was to investigate and assess the impact of Intellectual Capital and Good Corporate Governance on the Financial Performance of Banking Companies (Board of Directors, Audit Committee, and Independent Commissioners). 43 companies that were all banking companies were listed on the Indonesian Stock Exchange from 2019 to 2021, making up the study's population. The sample for this study, which consists of six banking organizations with the LQ45 index over the 2019–2021 research period, was chosen using a purposeful sampling technique. This research makes use of secondary data from the company's annual report. The GCG variable represented by the board of directors has a positive impact on return on assets (ROA), and intellectual capital also affects financial performance, according to the validity and reliability tests employed in this study.